Amazonian Lower Cretaceous North Tocantins State (Brazil) dinosaur track site: conservation significance - Tavares, Lanuze Fabielly (2015)
Fil: Tavares, Lanuze Fabielly. Campus de Porto Nacional, Laboratório de Paleobiologia, Universidade Federal do Tocantins, Palmas; Brasil.